Vybrané aspekty elektronického marketingu a analýza elektronickej marketingovej komunikácie v praxi - Šebová, Miriam; Kuzma, Marek; Dobšinská, Kristína (Vysoké učení technické v Brně, Fakulta podnikatelská, 2011)
The pressure of globalization, digital era and the economic crisis changed the role and the form of marketing tasks. New concepts are emerging, such as viral marketing, guerilla marketing, social communities, but also companies as YouTube, Facebook, Twitter and others. Companies can get their marketing communication to a new level by correct understanding of the importance and capabilities, which these concepts hide inside. Purpose This paper is focused on the electronic marketing. Scientific aim The main objective of the paper is to analyze selected theoretical aspects of electronic marketing and to evaluate the marketing communication in the real company. The paper deals with the hypothesis that the electronic marketing could address the relatively big group of consumers in the short time and could be in this way effective marketing method. Methodology/methods The methodology is based on using “Google Analytics” tools. The paper is divided in two parts. The first part contains a short overview of forms, methods and characteristics of online marketing communication. The key advantage of electronic marketing is the possibility to measure and evaluate exactly the efficiency of marketing tools. The second part contains case study from the marketing communication in the real online store. In the paper is analyzing the preparation of marketing strategy and the marketing strategy with duration of 10 months. Findings/Conclusion The paper contains practical examples of using new methods (viral techniques, references) by concrete company. Results of the analysis showed, that the marketing strategy addressed about 60 000 people in 10 months, which could be evaluate like successful.
Selected Aspects of Electronic Marketing and the Analyze of Electronic Marketing in Practice
Keywords: electronic marketing; online marketing; online advertising; social communities; google analytics; marketing research